(R)-α-Lipoyl-Gly-l-Pro-l-Glu dimethyl ester as dual acting agent for the treatment of Alzheimer's disease. (December 2017) - Marinelli, Lisa; Fornasari, Erika; Di Stefano, Antonio; Turkez, Hasan; Arslan, Mehmet Enes; Eusepi, Piera; Ciulla, Michele; Cacciatore, Ivana
Abstract: In this study, effects of LA-GPE (R-α-Lipoyl-Gly-l -Pro-l -Glu dimethyl ester) and GPE (Gly-L-Pro-L-Glu) on the cytotoxic action of Aβ1–42 were tested with differentiated human neuroblastoma SH-SY5Y cells as cellular Alzheimer model via measurements of mitochondrial viability (MTT assay) and lactate dehydrogenase release (LDH assay). Effects of LA-GPE and GPE on acetylcholinesterase (AChE) activity, total antioxidant capacity (TAC) and total oxidative status (TOS) levels, and neural cell apoptosis and necrosis were also determined. In addition, biological safety of these novel formulations was evaluated in human blood cells using different cytotoxicity and genotoxicity assays. Our results indicated that both compounds could block Aβ1–42 induced cell death. LA-GPE reduced Aβ -induced AChE activity and oxidative stress, suggesting it as a multifunctional compound potentially valuable for the treatment of Alzheimer's disease (AD). Graphical abstract: Highlights: Multitarget compound for the treatment of Alzheimer's Disease LA-GPE as inhibitor of acetylcholinesterase LA-GPE counteracts oxidative stress in Alzheimer's Disease